2021
DOI: 10.1021/acs.jpclett.1c03750
|View full text |Cite
|
Sign up to set email alerts
|

Entropy in the Molecular Recognition of Membrane Protein–Lipid Interactions

Abstract: Understanding the molecular driving forces that underlie membrane protein–lipid interactions requires the characterization of their binding thermodynamics. Here, we employ variable-temperature native mass spectrometry to determine the thermodynamics of lipid binding events to the human G-protein-gated inward rectifier potassium channel, Kir3.2. The channel displays distinct thermodynamic strategies to engage phosphatidylinositol (PI) and phosphorylated forms thereof. The addition of a 4′-phosphate to PI result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 67 publications
3
21
0
Order By: Relevance
“…Resistively heated devices are most common, but heating or cooling has also been done with Peltier devices . vT-ESI has been used to measure protein, ,, , protein complex, ,,, and DNA complex unfolding pathways and kinetics, , to determine thermochemical values of protein ,, and peptide stability, and to determine binding energetics of small-molecule ligands. ,, Recently, El-Baba et al determined T m values of seven proteins from a mixture of ribosomal proteins using vT-ESI, illustrating the advantage of this technique for multiplexed measurements …”
Section: Introductionmentioning
confidence: 99%
“…Resistively heated devices are most common, but heating or cooling has also been done with Peltier devices . vT-ESI has been used to measure protein, ,, , protein complex, ,,, and DNA complex unfolding pathways and kinetics, , to determine thermochemical values of protein ,, and peptide stability, and to determine binding energetics of small-molecule ligands. ,, Recently, El-Baba et al determined T m values of seven proteins from a mixture of ribosomal proteins using vT-ESI, illustrating the advantage of this technique for multiplexed measurements …”
Section: Introductionmentioning
confidence: 99%
“…Electrospray ionization of large (100 kDa to MDa) biomolecules produces a distribution of multiply charged ions, and each of the charge states is further broadened by their isotopic distribution as well as salts and adducts. These broader peak widths impose limitations for many types of mass spectrometry-based biochemical and biophysical studies, especially studies of protein–metal, protein–lipid, protein–protein, and protein–nucleotide interactions. These limitations may in some cases be overcome by combining charge-reducing reagents to provide greater separation between charge states.…”
Section: Introductionmentioning
confidence: 99%
“…While traditional solution-based techniques can be used to robustly examine temperature-dependent interactions between biomolecules and their ligands, they generally report on the ensemble average of ligand-bound states present in solution. Recent work leveraging the molecular resolution of nMS has shown that species-resolved thermodynamic analysis is possible. Combined with nMS, variable-temperature ESI (vT-ESI) allows for thermodynamic measurements of solution-phase structures with the benefit of mass separation. ,, This type of species-specific thermodynamic analysis can be especially valuable for complex or heterogeneous protein–ligand systems where the binding mechanism fundamentally changes as a result of a perturbation or shift in conditions without a measurable alteration to the observed Gibbs free energy (Δ G ). In these cases, enthalpic and entropic contributions to the Gibbs free energy shift in opposite directions, a phenomenon known as enthalpy–entropy compensation (EEC). , …”
Section: Introductionmentioning
confidence: 99%